The body writing and myth of the writer : Psychological critic analysis of Place des fêtes, Hermina and La fête des masques of Sami Tchak - (:unkn) unknown (My University, 2016)
In the heart of the aesthetic transformations of African literature of French expression, a special form of writing that breaks with the dull and linear narrative of the writers of the post-colonial period appears. Also, this new way of writing gives way to a new generation of francophone writers who offers readers a more raw, more sensual, more sexual literature. It is now intended to criticize social mores through the description of various characters from novels which are prey to the complexity of their intimate world. This new form of writing has enrolled us in a current literary trend that allows to introduce the universal character in the intimacy. In fact, the peculiarity of our thesis lies in its ability to lead the reader to perceive the link that may exist between the writing of the body and the quest for identity in contemporary literature of francophone Africa. This would be possible through the analysis of psychological critics of some literary works such as those of the Franco-Togolese writer Sami TCHAK. This research leads the reader to wonder how the writing of the body, through that of sexuality, can convey a literary discourse capable of allowing the writer to have a better understanding of himself. This aesthetic choice of transgression seems to actually be a pretext for the stylistic reconfiguration of contemporary African literature thanks to this new generation of writers.
Keywords: African Research